Adaptative Potential Students as Internal Resources Mastery Under Transformation of Society - Zavatska, Nataliya; Mykhaylyshyn , Ulyana (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article shows that the specificity of a holistic personality adjustment process in social systems is not confined only because of the peculiarities of its elements, such as the personal maturity, changes in the social conditions of the environment, and is determined by the interaction of structural components of the adaptive capacity of the individual. This maladjustment of one of these components will inevitably impact on the integrity of the individual adaptation process. It was determined that based on the analysis of the structural components of adaptation of the person (socially adapted situation, social need for adaptive, adaptive psychological need) there is the need to clarify the role of each of these components in the process of adaptation of the person. In the context of investigations under the holistic process of social adaptation of personality in social systems we mean active mutual adaptation of the individual and the social environment to each other in order to create a harmonious cooperation for the effective functioning of the individual in these social systems. Violation of this process or the implementation of its social disapproved or antisocial ways leads to the violation of the integrity of the adaptation process and it flows in unacceptable forms of society. It is emphasized that social exclusion leads to disruption of the socialization process, reflected in the increasing complexity of learning and the use of social roles, values and attitudes. In accordance with the social work we should pay attention to the replacement of anti-social norms, values and attitudes to prosocial. This process we treat as a social reinsertion - purposefully organized restructuring of the moral and valuable personality and behavioral areas that promotes the formation of social and value orientations and behavior. It was stated that the whole process of social adaptation of the person can provide awareness and reflection of environmental changes in the social systems of the environment; activity of the person in the regulation of adaptive capacity; transformation of adaptive capacity into more complex and sophisticated forms of interaction with the surrounding reality